Can Serum Tenascin-C Be Used as a Marker of Inflammation in Patients with Dilated Cardiomyopathy? - Alyaa A. Kotby; Manal M. Abdel Aziz; Waleed M. El Guindy; Amira N. Moneer (International Journal of Pediatrics)
Background. Tenascin-C (TN-C) is an extracellular matrix glycoprotein that appears at sites of inflammation in cardiac pathologies. Aim of the Work. To evaluate the role of TN-C as a marker for active inflammation in children with dilated cardiomyopathy (DCM). Subjects and Methods. 24 consecutive patients with primary nonfamilial DCM aged 6–72 months (mean 45.19±11.03) were divided into group I, twelve patients with acute onset DCM (<6 months duration), and group II, twelve patients with chronic DCM (>6 months duration), and compared to 20 healthy age- and sex-matched controls. Investigations included estimation of serum TN-C and echocardiographic evaluation using M-mode and 2D speckle tracking echocardiography (STE). Results. Serum TN-C showed a higher significant statistical elevation among patients than controls (P<0.001) and in group I than group II (P<0.001). EF was significantly decreased, and LVEDD and EDV increased in patients than controls and in GI than GII. STE showed a statistically significant difference in global peak strain longitudinal (GPSL) average in patients than controls (P<0.05) and between GI and GII (P<0.001). STE wall motion scoring showed normokinesia (33.5%), hypokinesia (8.33%), and akinesia (50%) in GI and hypokinesia (100%) in GII. There was a statistically significant positive correlation between serum TN-C and GPSL average. Conclusions. Increased serum TN-C can be used as a marker of inflammation in DCM and is associated with the severity of heart failure and LV dysfunction as detected by STE.